Biomechanical Evaluation of Proximal Hamstring Repair: All-Suture Anchor Versus Titanium Suture Anchor. Issue 1 (30th December 2019) - Otto, Alexander; DiCosmo, Alyssa M.; Baldino, Joshua B.; Mehl, Julian; Obopilwe, Elifho; Cote, Mark P.; Imhoff, Andreas B.; Beitzel, Knut; Mazzocca, Augustus D.; Coyner, Katherine
Background: Proximal hamstring avulsions are severe tendon injuries and are commonly sports-related. Open and endoscopic techniques as well as different anchor configurations have already been described for proximal hamstring repair. Novel all-suture anchors have been developed to provide decreased bone loss during placement and reduced occupied bone volume when compared with titanium suture anchors. Hypothesis: Complete proximal hamstring avulsions repaired with all-suture anchors will demonstrate equal load to failure and comparable displacement under cyclic loading when compared with titanium suture anchors. Study Design: Controlled laboratory study. Methods: Complete proximal hamstring avulsions were created in 18 paired cadaveric specimens (mean ± SD age, 63.0 ± 10.4 years). Either all-suture anchors or titanium suture anchors were used for repair. Cyclic loading from 10 to 125 N at 1 Hz was performed for 1500 cycles with a material testing machine. Displacement was assessed along anterior and posterior aspects of the tendon repair with optical tracking. Specimens were loaded to failure at a rate of 120 mm/min. Displacement, load to failure, and repair construct stiffness were compared between matched pairs with the Wilcoxon signed-rank test. Correlations were determined by Spearman rho analysis. Results: The all-suture anchors showed significantly higher load-to-failure values when compared with the titanium anchor repairs (799.64 ± 257.1 vs 573.27 ± 89.9 N; P = .008). There was no significant difference in displacement between all-suture anchors and titanium suture anchors at the anterior aspect (6.60 ± 2.2 vs 5.49 ± 1.1 mm; P = .26) or posterior aspect (5.87 ± 2.08 vs 5.23 ± 1.37 mm; P = .678) of the repaired hamstring tendons. Conclusion: All-suture anchors demonstrated similar displacement and superior load to failure when compared with titanium suture anchors. Clinical Relevance: The results of this study suggest that all-suture anchors are an equivalent alternative to titanium suture anchors for proximal hamstring avulsion repair.